К.СУЛТАНОВТЫӉ «ӨМИР ДӘПТЕРИ» ШЫҒАРМАСЫНДА ХАЛЫҚ НАҚЫЛ - МАҚАЛЛАРЫНЫӉ КӨРКЕМЛИК ХЫЗМЕТИ - Асенбаева, Г.Х. (FAN va JAMIYAT, 2022)
In this article the skillful use of proverbs and sayings that based on psychological parallelism in describing the character and motion of hero in K.Sultanov’s work “Omir dapteri” is analysed wish examples. Therefore, In K. Sultanov’s work “Omir dapteri” determined the issues of national folklore, in ofher words, artistic skill of writer in using proverb and sayings.